Risk of adverse outcome in patients referred by emergency medical services in Switzerland (Swiss Medical Weekly, 2017)
AIMS OF THE STUDY Comparison of outcomes between different emergency medical services (EMS) is difficult and lacking in Switzerland. Therefore, knowledge about the inherent risks of EMS-referred patients is important. Targeted interventions may benefit these patients by optimising resource allocation. We therefore aimed to study outcomes in EMS-referred patients presenting to a Swiss emergency department (ED). METHODS Prospective observational study in all patients presenting to the ED of Basel University Hospital. Mode of referral was recorded (EMS or other). Univariate and multivariate linear, Poisson and logistic regression models were used. Crude and age/gender adjusted associations between mode of referral and outcomes were calculated. Outcomes were shown for admission, length of stay (LOS), in-hospital, and 1-year mortality. RESULTS Of 5634 patients presenting in the inclusion period, 4703 were screened, 4544 were included and 4287 were followed up for 365 days. Associations between EMS referral and several adverse outcomes were found and expressed as odds ratios (ORs) and geometric mean ratios (GMRs): hospital admission (OR 3.8, 95% CI 3.2–4.5; p